2008
DOI: 10.1348/014466607x224521
|View full text |Cite
|
Sign up to set email alerts
|

Is Kate Winslet more American than Lucy Liu? The impact of construal processes on the implicit ascription of a national identity

Abstract: In four studies, we investigated the role of person construal on the implicit ascription of a national identity. Participants completed Implicit Association Tests (Studies 1 and 3) or Go/No-go Association Tasks (Studies 2 and 4) assessing the extent to which the concept American was linked to an Asian American celebrity (Lucy Liu) and to a White European celebrity (Kate Winslet). In contrast to explicit responses, the Asian American target was implicitly regarded as being less American than the White European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 67 publications
8
61
0
Order By: Relevance
“…P-IAT was moderately but significantly correlated with approach/avoidance tendency while the other two versions were not. These results, albeit correlational and preliminary, are in line with the idea that different IAT versions may be associated with different task sets (see also Devos & Ma, 2008). These results may be explained by the P-IAT's preferential activation of emotion, response, and motor processes (e.g., Carver & Scheier, 2002;Ellsworth & Scherer, 2003;Frijda, 2000).…”
Section: General Conclusionsupporting
confidence: 75%
See 1 more Smart Citation
“…P-IAT was moderately but significantly correlated with approach/avoidance tendency while the other two versions were not. These results, albeit correlational and preliminary, are in line with the idea that different IAT versions may be associated with different task sets (see also Devos & Ma, 2008). These results may be explained by the P-IAT's preferential activation of emotion, response, and motor processes (e.g., Carver & Scheier, 2002;Ellsworth & Scherer, 2003;Frijda, 2000).…”
Section: General Conclusionsupporting
confidence: 75%
“…In keeping with our views, some authors have suggested that the specific characteristics of different IAT versions might partly determine their findings (Steffens, Kirschbaum, & Glados, 2008) and that different IAT versions might not measure the exact same ''attitudes'' but different representations elicited by the relation of the specific stimuli sets to be classified and the category labels (e.g., Blair, 2002;Devos & Ma, 2008;Steffens et al, 2004;see also De Houwer, 2002;Govan & Williams, 2004). Moreover, the IAT is thought to be more sensitive to mental representations at the level of categories than at the level of the category's exemplars (Nosek et al, 2006, p. 24;Nosek, Greenwald, & Banaji, 2005).…”
supporting
confidence: 79%
“…For example, in the American context, although people may endorse principles that support a civic conception of national identity, nationality is implicitly granted to some ethnic groups more easily than others suggesting a more ethnic conception of nationality (e.g., Devos & Banaji, 2005;Devos, Gavin, & Quintana, 2010;Devos & Ma, 2008;Yogeeswaran & Dasgupta, 2010;Yogeeswaran, Dasgupta, Adelman, Eccleston, & Parker, 2011;Yogeeswaran, Dasgupta, & Gomez, 2012). For example, when a sample of mostly White American participants were asked to define what makes someone a true American, they tended to endorse a number of civic national identity statements such as "vote in elections", "respect America's political institutions and laws", etc.…”
Section: Implicit and Explicit Construals Of Nationalitymentioning
confidence: 99%
“…That is, people may report that private expressions of ethnic identity are acceptable for any group of Americans while public expressions are not acceptable for any Americans. An alternative hypothesis comes from several studies which have found that Americans of all races implicitly perceive Whites to be more authentically American than any ethnic minority group (Devos & Banaji, 2005;Devos, Gavin, & Quintana, 2010;Devos & Ma, 2008;Yogeeswaran & Dasgupta, 2010). These studies suggest that the prototypical "true" American is automatically envisioned to be White rather than of any other race.…”
mentioning
confidence: 99%